2021
DOI: 10.3389/fmicb.2020.618168
|View full text |Cite
|
Sign up to set email alerts
|

Early Drug Development and Evaluation of Putative Antitubercular Compounds in the -Omics Era

Abstract: Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. According to the WHO, the disease is one of the top 10 causes of death of people worldwide. Mycobacterium tuberculosis is an intracellular pathogen with an unusually thick, waxy cell wall and a complex life cycle. These factors, combined with M. tuberculosis ability to enter prolonged periods of latency, make the bacterium very difficult to eradicate. The standard treatment of TB requires 6–20months, depending on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 138 publications
(157 reference statements)
0
2
0
Order By: Relevance
“…The use of transcriptomic analysis for understanding a drug’s mode of action provides useful insights into the target pathways affected by the action of the compound ( 36 ). Thanks to the contribution of transcriptomics, we showed that 11726172 treatment perturbs both the metal homeostasis and the cytoplasmic redox potential in mycobacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The use of transcriptomic analysis for understanding a drug’s mode of action provides useful insights into the target pathways affected by the action of the compound ( 36 ). Thanks to the contribution of transcriptomics, we showed that 11726172 treatment perturbs both the metal homeostasis and the cytoplasmic redox potential in mycobacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, four first-line antibiotics used in the treatment of TB (isoniazid–INH, rifampicin–RMP, ethambutol–EMB, pyrazinamide–PZA) and some other drugs which can be administered to patients infected with resistant strains M. tuberculosis Although TB is curable and preventable, multidrug-resistant TB (MDR-TB) and extensively drug-resistant strains of M. tuberculosis (XDR-TB) remain a global burden rendering the standard treatment ineffective 2 . It is estimated that about 0.5 million of MDR-TB cases reported annually worldwide and nearly 14,000 XDR-TB cases were originated from 81 countries 3 , 4 . Additionally, the management of TB was further aggravated as MDR-TB developed resistant to two of the first-line drugs; RMP and INH, while XDR-TB is resistant to the four essential antitubercular drugs and at least one of the injectable second-line drugs such as amikacin, capreomycin, or kanamycin 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%